2022
DOI: 10.1186/s42238-021-00113-w
|View full text |Cite
|
Sign up to set email alerts
|

Olivetolic acid, a cannabinoid precursor in Cannabis sativa, but not CBGA methyl ester exhibits a modest anticonvulsant effect in a mouse model of Dravet syndrome

Abstract: Objective Cannabigerolic acid (CBGA), a precursor cannabinoid in Cannabis sativa, has recently been found to have anticonvulsant properties in the Scn1a+/- mouse model of Dravet syndrome. Poor brain penetration and chemical instability of CBGA limits its potential as an anticonvulsant therapy. Here, we examined whether CBGA methyl ester, a more stable analogue of CBGA, might have superior pharmacokinetic and anticonvulsant properties. In addition, we examined whether olivetolic acid, the biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This so-called “entourage effect” could induce synergistic interactions among phytocannabinoids, and this effect could explain various pharmacokinetic properties, including substrate specificity, half-life, and regulatory functions with respect to target molecules [ 15 ]. CBDA concentrations were higher following cannabis extract administration than when administered as a single molecule in a mouse study, indicating that the crude extract provides a natural vehicle to substantially enhance CBDA concentrations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This so-called “entourage effect” could induce synergistic interactions among phytocannabinoids, and this effect could explain various pharmacokinetic properties, including substrate specificity, half-life, and regulatory functions with respect to target molecules [ 15 ]. CBDA concentrations were higher following cannabis extract administration than when administered as a single molecule in a mouse study, indicating that the crude extract provides a natural vehicle to substantially enhance CBDA concentrations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study was designed to gain insights into the prospective therapeutic properties of 1b and its analogs. Only one phytochemical investigation of 1b was found in the literature [ 6 ]. In contrast, the antibacterial activities of 2b and 3b against S. aureus have been well studied [ 10 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study revealed that despite its low brain penetration, the biosynthetic precursor molecule 1b exhibited a moderate anticonvulsant effect in a mouse model of Dravet syndrome, with comparable potency to the known anticonvulsant cannabinoid, CBD [ 6 ]. To the best of our knowledge, no other activity has been reported for 1b .…”
Section: Introductionmentioning
confidence: 99%
“…This has inspired research addressing whether other less well characterized phytocannabinoids might similarly have anti-seizure properties. Indeed, recent studies have shown that several minor cannabinoids have anti-seizure effects in mouse models including CBGA, CBDVA, CBCA, and CBC ( Anderson et al, 2019b ; Anderson et al, 2021a ; Anderson et al, 2021b ; Anderson et al, 2022 ; Benson et al, 2022 ). However, the molecular mode of action of these compounds is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of CBD as an approved medicine has generated substantial interest in whether other phytocannabinoids might similarly be developed as novel anti-convulsants. We have recently reported that the lesser studied phytocannabinoids, cannabigerolic acid (CBGA), cannabidivarinic acid (CBDVA), cannabichromenic acid (CBCA) and cannabichromene (CBC) were anti-convulsant in a mouse model of DS ( Anderson et al, 2021a ; Anderson et al, 2021b ; Anderson et al, 2022 ). However, the mode of action of these compounds remains enigmatic, particularly at epilepsy-relevant drug targets.…”
Section: Introductionmentioning
confidence: 99%